Pelatihan dan Pendampingan Pembukuan Kepada UMKM Jasa Pengambilan Sampah Djong Larahan - Nike Larasati; Riska Fii Ahsani; Setia Murningsih (Yayasan Literasi Sains Indonesia, 2025)
Djong Larahan is a service business engaged in household waste collection. Djong was established in 2021, and is located in Dukuh Tandan RT 002 RW 001 Jatimulyo Village, Pedan District, Klaten Regency, Central Java. Currently Djong Larahan has 205 household members from 4 villages consisting of 2 sub-districts. Djong members start from households, cafes and shops around the Pedan sub-district. With rapid development, Djong Larahan has obstacles in the bookkeeping process due to the uncertain monthly fee withdrawal schedule and changing officers in the withdrawal, which results in Djong Larahan's financial bookkeeping. The solution provided is to provide bookkeeping knowledge and skills to the Djong Larahan team, by means of training, mentoring and monitoring. The results of this assistance contributed well to the DJong Larahan bookkeeping system, which currently uses excel with templates made by the assistance team and in the withdrawal system given a cut sheet that can be used as proof of payment every time. The impact of the results of the assistance is that Djong Larahan's finances are more organized.